SCHOOL BULLYING BEHAVIOR IN SCHOOL MUHAMMADIYAH ELEMENTARY SCHOOL 15 SURAKARTA - Yafi, Muhammad Sohib; Muhroji, Muhroji; Arifin, Achmad Januar; Fitri, Annisa (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to describe bullying behavior in SD Muhammadiyah 15 Surakarta,. This type of research is qualitative research (Qualitative Research). Data collection techniques are conducted through interviews, and supporte d by observation and documentation. The validity of the data using source triangulation. Data analysis techniques performed from the reduction stage, display data, and verification/conclusion. The results showed that the perpetrators of school bullying in SD Muhammadiyah 15 Surakarta performed by students, namely Riyan, Riko and Bagus. The causes of school bullying are the school climate, family, social environment, and impressions or media. School bullying behavior is common during break times. The most common type of school bullying is exclusion. Next is threatening, scolding, commanding, mocking, yelling, pointing with fingers to the face, cheering, forcing, pushing the beat with the hand and the broom handle. The role of teachers in dealing with school bullying is to provide counseling to students in need of assistance, including addressing those involved in bullying. The role of schools in relation to bullying is cooperation with the parents through the assistance provided for both victims and perpetrators of bullying. The efforts of teachers in overcoming bullying actors is to direct the perpetrators on the positive and grow harmonious relationships between children and parents